Model Dakwah Networking: Analisis Dakwah IDIAL-MUI dalam Penutupan Lokalisasi Prostitusi di Jawa Timur - AS, Sunarto (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This article seeks to discuss in depth the model of networking proselytising conducted by the Asociation of Preachers in Localization Area (IDIAL) and the Indonesian Ulema Council (MUI) of East Java in attempting to close down prostitution practices in East Java. Using a participatory approach, this study concluded that the IDIAL-MUI networking da'wah model used both structural and cultural approaches. The structural approach was carried out by building and strengthening power networks, namely bureaucracy, politics and the military in the process of closing the